2020
DOI: 10.1088/1755-1315/419/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of modulus elasticity of Falling Weight Deflectometer (FWD) towards Light Weight Deflectometer (LWD) laboratory

Abstract: Develop a new laboratory LWD and this study aims to analyse the laboratory version of the LWD with the field version of the LWD currently developed by Bina Marga, Indonesia. Basically, the working principle of the developed laboratory LWD is same as the LWD equipment in the field, which is an instrument that can measure deflection value and modulus of elasticity through load impulses arising from a load with a specific weight dropped at a certain height on a plate surface with a particular area on a pavement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Through study performed at the Road and Bridge Research Center, the following will describe numerous varieties of LWD, including those manufactured outside and those produced by Indonesians (Puslitbang). The Pusjatan LWD is the outcome of research [30] undertaken during the 2012 and 2013 budget years at the Research and Development Center for Roads and Bridges (Figures 2 and 3). West Java has used the Pusjatan LWD on various parts of dirt roads.…”
Section: Light Weight Deflectometer (Lwd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Through study performed at the Road and Bridge Research Center, the following will describe numerous varieties of LWD, including those manufactured outside and those produced by Indonesians (Puslitbang). The Pusjatan LWD is the outcome of research [30] undertaken during the 2012 and 2013 budget years at the Research and Development Center for Roads and Bridges (Figures 2 and 3). West Java has used the Pusjatan LWD on various parts of dirt roads.…”
Section: Light Weight Deflectometer (Lwd)mentioning
confidence: 99%
“…Light Weight Deflectometer (LWD) Modification is an alternate instrument for quality control of compaction. It can be shown that employing this Modified LWD tool as a quality control tool has various benefits, including efficiency in terms of time, money, and the number of workers necessary [2]. The Binamarga (Indonesian Road Development Office) 2018 standard mandates the utilization of LWD in the inspection process for granular layer compaction in road building projects [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is an archipelago where the Indo-Australian, Eurasian, and Pacific tectonic plates converge [1]. Indonesia is an area of intense volcanic and seismic activity due to the interactions between these tectonic plates [2,3]. The process of plate dynamics, which is quite intense, has also formed a distinct and quite varied relief of the earth's surface, ranging from mountainous regions with steep slopes that seem to imply a high potential for landslides to gently sloping coastal regions with potential threats of flooding, subsidence, and tsunamis [4,5].…”
Section: Introductionmentioning
confidence: 99%